Tissue-specific regulation of epidermal contraction during Caenorhabditis elegans embryonic morphogenesis. Issue 7 (11th May 2021) - Drewnik, Elizabeth D; Wiesenfahrt, Tobias; Smit, Ryan B; Park, Ye-Jean; Pallotto, Linda M; Mains, Paul E
Abstract: Actin and myosin mediate the epidermal cell contractions that elongate the Caenorhabditis elegans embryo from an ovoid to a tubular-shaped worm. Contraction occurs mainly in the lateral epidermal cells, while the dorsoventral epidermis plays a more passive role. Two parallel pathways trigger actinomyosin contraction, one mediated by LET-502/Rho kinase and the other by PAK-1/p21 activated kinase. A number of genes mediating morphogenesis have been shown to be sufficient when expressed either laterally or dorsoventrally. Additional genes show either lateral or dorsoventral phenotypes. This led us to a model where contractile genes have discrete functions in one or the other cell type. We tested this by examining several genes for either lateral or dorsoventral sufficiency. LET-502 expression in the lateral cells was sufficient to drive elongation. MEL-11/Myosin phosphatase, which antagonizes contraction, and PAK-1 were expected to function dorsoventrally, but we could not detect tissue-specific sufficiency. Double mutants of lethal alleles predicted to decrease lateral contraction with those thought to increase dorsoventral force were previously shown to be viable. We hypothesized that these mutant combinations shifted the contractile force from the lateral to the dorsoventral cells and so the embryos would elongate with less lateral cell contraction. This was tested by examining 10 single and double mutant strains. In most cases, elongation proceeded without a noticeable alteration in lateral contraction. We suggest that many embryonic elongation genes likely act in both lateral and dorsoventral cells, even though they may have their primary focus in one or the other cell type.